The Role of Educational Attainment in Human Development: An Empirical Study of West Sumatra - Marna, Jean Elikal; Rahim, Febria (Universitas Negeri Padang, 2025)
This study investigates the relationship between educational indicators. Mean Years of Schooling (RLS), Expected Years of Schooling (HLS), School Participation Rate (APS), and the Percentage of Population with Secondary and Higher Education (PP) and the Human Development Index (IPM) in West Sumatra from 2014 to 2023. Utilizing regression analysis, the findings reveal a consistently positive and significant correlation between all independent variables and the dependent variable, IPM. Among these, the proportion of the population with secondary and higher education exhibits the strongest influence, highlighting the critical role of advanced educational attainment in human development. The results align with human capital theory and existing literature, emphasizing education’s centrality in improving health, income, and overall quality of life. This research offers important insights for policymakers aiming to enhance educational access and quality as a strategy for regional development and social equity.